Pembentukan Self-Disclosure Pengguna Dating Apps Tinder Dalam Komunikasi Interpersonal Untuk Menemukan Pasangan Hidup - Dian Kartika Fitri; Irwansyah Irwansyah (CV. Publikasi Indonesia, 2023)
The more technology develops, the more cell phone users will also be from teenagers to the elderly. People utilize various features or applications available on their cellphones for the interests they want too, one of which is the tinder application. The tinder application as a dating app is very much loved by teenagers or adults to find acquaintances such as new friends or even looking for a partner, where they use the application to be able to describe themselves to attract the attention of the opposite sex called self-disclosure. Self-disclosure in the tinder app will show an increase in a person's use of information and communication technology, especially for interpersonal communication. So the formation of self-disclosure in this tinder application is very important to get to know each other. This research uses self-disclosure theory with the Johari Window model which has four panels in self-disclosure. This research uses qualitative research methods with a descriptive analysis approach with two sources who are 24 years old and 22 years old. There are two discussions, namely about how the formation of self-disclosure to find a life partner and also how the application of the Johari Window model in using the tinder application.